Investigating the quality of Service in chain stores using SERVQUAL approach (Case Study: Refah Stores on Alborz Province) - Salamzadeh, Yashar; Zadeh, Mohammad Ali Mohammad (Archives of Business Research, 2015)
In Today's competitive environment, organizations must evaluate the quality of their products or Service. If it is so bad, they enhance their quality of service and they maintain their customers and competitive position. This is more important in service organizations. One of these methods is the use of SERVQUAL model. The aim of this study was to assess the quality of Service with the goal of determining the quality of Service provided to customers in chain stores Refah Alborz Province and enhancement of quality of the customer's perspective. The results can be used in the Stores Refah and other similar stores. The data collection tool was questionnaires that for its reputation, the comments of experts, professors, experts, and consultants have been used. Cronbach's alpha was used in relation to the reliability that its rate was 0.923. The population of the research includes all customers in chain stores is being Alborz province that was an unlimited number. The sample is 384, which randomly selected through a Crejeci and Morgan Table. However, for more accurate and more confident calculations, researchers distributed 500 questionnaires, of which 428 questionnaires were referred to, and hypotheses are based on 428 questionnaires. The designed questionnaire evaluates qualities of Service in six dimensions (physical environment and tangibility, empathy, assurance, reliability, availability and responsibility). The results suggest that there is a gap between customer expectations of service quality and their comprehension of this matter. There is a positive and significant relationship between quality of Service and Service.